Pectoralis (PecS) nerve block 1 for port-a-cath removal and central venous catheter (CVC) replacement - Massimo Renzini; Umberto Ripani; Luisa Golia; Fulvio Nisi; Fabio Gori (Medicinski glasnik, 2020)
Aim: The use of PecS block 1 as perioperative analgesia for a central catheter removal-reimplantation combined procedure. Methods: A 55-year-old woman suffering from peritoneal metastases from gastric cancer needed to have a port-a-cath implanted for infection removed and to have a central venous catheter (CVC) implanted in the homolateral axillary vein due to patient's history of deep vein thrombosis of the right upper limb. We used PECS 1 block for perioperative analgesia. Results: Compared to the traditional catheter implantation technique, reduction in the doses of local anaesthetics, shortening in the execution time, less intra-procedural bleeding, better patient's compliance, and no need for a rescue dose of local anaesthetic were observed. Conclusion: The PEC1 block was effectively and safely used to remove an infected port-a-cath and to place a CVC on the same side. We hypothesize that it may be useful also for simple port-acath positioning.
Keywords: complication; local anaesthesia; outcomes; pectoralis block; port-a-cath